Tonsillectomy discharge information - An improvement in both patient safety and satisfaction. Issue 2 (8th January 2014) - Carter, Alison; Warner, Elinor; Roberton, Andrew; Liu, Xiaxin; Abdul-Hamid, Ayeshah; Natt, Ravinder; Hopkins, Claire
Abstract: Approximately 20, 000 adult and 25, 000 paediatric tonsillectomies are performed each year in England. 0.9% of these patients return to theatre for post-tonsillectomy bleeding. The Royal College of Surgeons of England (RCSEng) have produced guidelines regarding emergency surgery, with standards for tonsillectomy discharge information. We audited our compliance with these guidelines and patient satisfaction regarding the information currently provided. Theatre records identified all tonsillectomies carried out between December 2012 and February 2013. 71 patients and their electronic discharge information were reviewed for post-operative bleeding information. Each patient was contacted, with a second call made to those who did not answer. 35 patients took part in our telephone questionnaire. Only 35% of patients had post-operative bleeding information on their discharge summary. 51% received no written information either in clinic or on the day of surgery, 66% recalled a verbal explanation. Only 54% knew to go to A&E if they experienced bleeding. 40% were not satisfied with their discharge information, stating that they wanted to know about bleeding, recovery expectations, and information regarding oral intake. A focus group was formed to discuss potential solutions to the audit outcomes and a tonsillectomy leaflet was produced inline with the trust patient information template. It contained specific instructions regarding bleeding and the nearest A&E contact details. It was reviewed by three tonsillectomy patients and their feedback regarding further information on post-operative diet, throat appearance and pain expectations was incorporated. A second cycle of the audit took place between August and September 2013. Results showed improvement, with 83% receiving an information leaflet and 100% a verbal explanation. 100% of patients were satisfied with their discharge information and 100% knew what to do if they bled. As a result we now meet the standards set out by the RCSEng and have increased our patient safety and satisfaction rates.